White matter microstructure of the cingulum bundle and the uncinate fasciculus in primary and secondary callous-unemotional traits - Schalk, Luisa; Sethi, Arjun; Saam, Melanie C.; Flamarique, Itziar; Naaijen, Jilly; Dietrich, Andrea; Hoekstra, Pieter J.; Banaschewski, Tobias; Aggensteiner, Pascal; Holz, Nathalie E.; Baumeister, Sarah; Borràs, Roger; et al. (European child & adolescent psychiatry, 2025)
Callous-unemotional (CU) traits appear to be linked to differences in neural networks, including the uncinate fasciculus (UF) and cingulum bundle (CB). It has recently been suggested that CU traits are comprised of primary and secondary subtypes based on the relative co-occurrence of internalising symptoms. Here, we explored the white matter microstructure of these subtypes. White matter microstructure of the UF and CB was analysed in youths (aged 8-18; n = 121; females = 31) recruited through Europe-based multisite studies. Our sample comprised a control (n = 53) and a case group with disruptive behaviour disorders (DBDs) (n = 68) with low and high levels of CU traits. The case group was further split into primary (n = 49) and secondary (n = 14) subgroups. Compared to the control group, the case group showed decreased mean diffusivity in the right ventral CB (p =.023, uncorrected). Within our case group, higher scores on the ‘unemotional’ subscale of the Inventory of Callous Unemotional Traits were associated with decreased axial diffusivity (p =.02, uncorrected) and mean diffusivity (p =.013, uncorrected) in the dorsal CB in youths with primary CU traits, but the opposite in those with secondary CU traits. Post hoc analyses found that the left hemisphere drove these effects. The relationship between CU traits and dorsal CB microstructure appears dependent on the presence of internalising symptoms and CU traits subcomponents. A fractionation may lead to a better understanding of the aetiology of DBDs and more focused treatment options.